Advancing Performance and Unfolding Mechanism of Lithium and Sodium Storage in SnO2 via Precision Synthesis of Monodisperse PEG‐Ligated Nanoparticles. Issue 26 (26th May 2022) - Zhao, Shiqiang; He, Yanjie; Wang, Zewei; Bo, Xiaoxu; Hao, Shumeng; Yuan, Yifei; Jin, Huile; Wang, Shun; Lin, Zhiqun
Abstract: Low conductivity and tin coarsening issues hinder the utility of tin dioxide as anode for lithium and sodium ion batteries. To significantly advance the electrochemical performance and systematically unfold the energy storage mechanism of SnO2, monodisperse poly(ethylene glycol)‐ligated SnO2 nanoparticles are in situ crafted with star‐like poly(acrylic acid)‐block‐poly(ethylene glycol) diblock copolymers as nanoreactors and uniformly confined in layer‐by‐layer stacked graphene oxide matrix (denoted SnO2 @PEG‐GO). Remarkably, SnO2 @PEG‐GO nanohybrids manifest fully reversible three‐step lithiation‐delithiation reactions of SnO2 with an ultrahigh 100th discharge capacity of 1523 mAh g −1 at 100 mA g −1 . Moreover, SnO2 @PEG‐GO nanohybrids exhibit an ultrastable sodium storage capacity of 527 mAh g −1 after 500 cycles at 50 mA g −1, and the conversion reaction between Sn and SnO is uncovered as the primary reversible sodiation–desodiation reaction of SnO2 . Notably, in addition to buffering volume expansion of SnO2 nanoparticles, the synergy between PEG and GO promotes Li + or Na + ion and electron transfers and inhibits Sn coarsening at micro and macro scales. This work provides a robust strategy to realizing outstanding electrochemical properties and scrutinizing fundamental mechanisms that underpin the performance of active materials via surface polymer ligation, precise size control, and uniform graphene encapsulation. Abstract : Monodisperse PEG‐ligated SnO2 nanoparticles with an average diameter of 4.1 ± 0.4 nm are precisely crafted using star‐like poly(acrylic acid)‐block‐poly(ethylene glycol) (PAA‐b‐PEG) diblock copolymer as nanoreactor and homogenously encapsulated with graphene oxide (GO) matrix. The short ionic transfer distance, high electron/ion conductivity, and robustly inhibited Sn coarsening render fully reversible lithium storage reaction and ultrastable sodium storage capability of SnO2 .